2016
DOI: 10.24926/iip.v7i1.419
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Pharmacy Law Education Utilizing a Mock Board of Pharmacy Meeting

Abstract: A thorough understanding of pharmacy law by students is important in the molding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Before this project, historically, mock trials were scarcely employed in pharmacy education, found only in isolated instances, and without repeated and deliberate assessment for competencies and outcomes; only one study previously reported having students as active participants in a mock trial albeit with roles that were scripted for the students by faculty or actual court cases (van Dusen, 1998;Broeseker & Jones, 1999;Spies, 2008;Bess et al, 2016;Rosenberg et al, 2018). Debates, however, have been employed in pharmacy education for active learning and assessment activities in various contexts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Before this project, historically, mock trials were scarcely employed in pharmacy education, found only in isolated instances, and without repeated and deliberate assessment for competencies and outcomes; only one study previously reported having students as active participants in a mock trial albeit with roles that were scripted for the students by faculty or actual court cases (van Dusen, 1998;Broeseker & Jones, 1999;Spies, 2008;Bess et al, 2016;Rosenberg et al, 2018). Debates, however, have been employed in pharmacy education for active learning and assessment activities in various contexts (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Law courses often consist of traditional lectures with case studies. Teaching a subject that is considered less stimulating than the practical topics to be used in clinical practice is a challenge [5]. One of the questions to consider when thinking about the introduction of law courses into a health professional education is "what pedagogical modalities should be used?"…”
Section: B Teaching Law In the Health Sectormentioning
confidence: 99%
“…[ 6 ] In teaching Pharmacy Law and Ethics, educators are challenged to create an interesting and engaging method of educating students about a subject that is potentially considered to have little clinical relevance. [ 7 ] While CBL has proven to have some success in meeting this challenge in other health professions courses, [ 6 ] there is a lack of documented data on its use in teaching pharmacy law and ethics in SA, and at UKZN specifically. Early evaluation of the usefulness of and learner experience with CBL is therefore important to modify and enrich the current teaching methods, and to form a better learning approach with the active participation of students.…”
Section: Significance Of the Studymentioning
confidence: 99%